Total Synthesis of (+)-Hyacinthacine A6 and (+)-Hyacinthacine A7 - Smith, Julien; Kamath, Anushree; Greene, Andrew E.; Delair, Philippe (Synlett, 2014)
(+)-Hyacinthacines A6 and A7 have been synthesized from a common, late-stage intermediate, prepared in high yield through stereoselective [2+2] cycloaddition of dichloroketene to a chiral enol ether. The flexibility of aminonitrile chemistry is central to the approach.
Keywords: asymmetric synthesis; cycloaddition; glycosidase inhibitors; aminonitriles; iminosugars